Gender Inequality in Spain’s Official Music Charts: Neither Representation nor Success for Female Artists (2008–2020) - Cande Sánchez-Olmos (Journalism and Media)
This study seeks to investigate gender inequality in the Spanish’s official music charts from 2008 to 2020, using a quantitative methodology. The dataset comprises 1300 entries sourced from Promusicae’s official charts, evenly divided between albums and singles. Firstly, this analysis evaluates the frequency of artist representation; secondly, it assesses the success achieved by gender; and finally, it examines disparities in featured collaborations. The findings indicate that male artists appear almost three times more frequently than their female counterparts on both charts, achieve a higher amount of points, and dominate the role of featuring collaborations. Notably, Spanish female artists are predominantly absent from the top positions in the singles chart. Moreover, there is an absence of female bands in the top 50. The observed outcomes align with previous research concerning gender inequality in the United States and the United Kingdom, highlighting a persistent structural gender inequality within Spain’s music industry throughout the reviewed period, which systematically undermines the creativity of female artists.